TERRITORIAL FEATURES RESETTLEMENT OF THE POPULATION OF THE KHARKIV DISTRICT OF KHARKIV REGION - Сегіда, Катерина; Ткаченко, Надія (Human Geography Journal, 2016)
The article deals with characteristics of the territorial population distribution of the Kharkiv district of Kharkiv region. The general characteristic of the population settlement of the Kharkiv region is given. The Place of district is defended. The population density by administrative districts of the Kharkiv district is calculated and analyzed. The index of population concentration is reduced and characterized. The application center-graphical method by territorial characteristics in the research of population settlement is founded. The arithmetic mean, median and modal center and center of population gravity are calculated. The results are displayed cartographical. Analysis of neighborhood is given. The features of the population distribution on the territory of the Kharkiv district of Kharkiv region are identified and analyzed.